A Comprehensive Review of Harnessing Bioinformatics in Biochemistry: A New Era of Data-Driven Discoveries and Applications - Kimu, Amina Khatun (Control Systems and Optimization Letters, 2025)
The integration of bioinformatics into biochemistry has ushered in a new era of scientific discovery, leveraging computational power and big data to uncover molecular mechanisms, predict molecular interactions, and accelerate the development of therapeutics. This review explores the advancements in bioinformatics tools and techniques that are transforming biochemistry. By discussing key applications, such as protein structure prediction, genomic data analysis, and systems biology, this paper highlights the significant contributions of bioinformatics in biochemistry and its potential for future applications in personalized medicine, drug discovery, and disease modeling. A key factor in the advancement of biochemistry, bioinformatics has become a transformative field at the nexus of biology, computer science, and statistics. Using tools and methods from genomics, proteomics, drug discovery, and systems biology, this review examines how bioinformatics might be integrated into the study of biochemical processes. The study of multi-omics data, the use of machine learning techniques to find molecular patterns and biological insights, and the application of computational modeling for protein structure prediction are important subjects. The paper also looks at the difficulties in analyzing biological data on a big scale, such as problems with data quality, reproducibility, and the requirement for interdisciplinary cooperation. As new technologies like artificial intelligence and quantum computing become available, bioinformatics has the potential to completely transform our knowledge of biological systems and speed up the identification of new biomarkers and treatment targets. This era of data-driven science promises to enhance human health through advancements in personalized medicine and innovative solutions to complex biochemical challenges.